The Communication Strategy of Wasathiyah Da'wah by MUI in Supporting Government's Covid-19 Mitigation in Indonesia - ., Rosidi; Aisyah, Umi (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study examines the wasathiyah (moderate) da'wah communication strategy implemented by the Indonesian Ulema Council (MUI) in supporting government efforts to mitigate the COVID-19 pandemic impact in Indonesia. In a challenging pandemic situation, the role of MUI as a religious institution is crucial in conveying calming religious messages and building community solidarity. This study uses a qualitative method with a case study approach, where data is collected through in-depth interviews with MUI figures, document analysis, and participatory observation. The results of the study show that MUI implements four main strategies: (1) spiritual efforts through religious appeals and sermons, (2) issuing 12 fatwas related to worship during the pandemic, (3) forming task forces from the center to the regions and raising donations, and (4) holding national webinars for socialization. The supporting factors for the strategy are awareness of maqashid sharia and the view of COVID-19 as a universal humanitarian problem. Meanwhile, the inhibiting factor is the continued distrust of some people and religious figures regarding the existence of COVID-19. This study concludes that MUI's moderate and inclusive moderate da'wah approach contributes positively to supporting the government's efforts to overcome the impact of the pandemic in Indonesia. These findings can be a reference for other religious institutions in developing effective communication strategies during times of crisis.